Progression of keratoconus in children and adolescents. Issue 2 (3rd September 2021) - Meyer, Jay J; Gokul, Akilesh; Vellara, Hans R; McGhee, Charles N J
Abstract : Aims: To evaluate the rates of keratoconus progression and associated factors in eyes of children and adolescents. Methods: Retrospective, cohort study of individuals ≤18 years old at the time of keratoconus diagnosis and with at least 6 months of follow-up. Corneal tomography was performed using an Orbscan tomographer (Bausch & Lomb, Rochester, New York, USA) to determine whether progression occurred. Tomographic progression of keratoconus was defined as a change in any of the investigated parameters (keratometry values, KMAX, maximum anterior or posterior elevation, central pachymetry, thinnest pachymetry) beyond the limits of repeatability. Results: 148 eyes of 106 patients with a mean age of 15.2±2.5 years were studied over a mean follow-up period of 2.9±2.2 years. The overall rate of tomographic progression was 77.0% (114/148 eyes). Eyes that progressed had more advanced disease at presentation with higher anterior curvature (KMAX 55.4±6.3 vs 52.2±5.4 dioptres; p<0.01), posterior elevation (108.2±40.9 vs 86.3±35.6 µm; p<0.01) and lower central pachymetry measurements (442.1±56.7 vs 454.4±47.5 µm; p=0.01). Age at presentation, gender, atopy, documented eye rubbing, ethnicity and duration of follow-up were not significantly associated with progression in the multivariate analyses. There was a higher rate of bilateral progression if at least one eye had severe keratoconus (73.9%) compared with no severe keratoconus in either eye (36.8%; p=0.03). Conclusions: A high rate of progression was identified in keratoconic eyes of children and adolescents. More advanced disease at initial presentation may increase the risk of further keratoconus progression.